Nitrogen-Neutral Amino Acids Refinery: Deamination of Amino Acids for Bio-Alcohol and Ammonia Production - Choi, Kwon Young (ChemBioEng Reviews, 2021)
Amino acids are a valuable bioresource that contains both the acid form of carbon and the amine group of nitrogen. Amino acids not only constitute proteins and the building blocks for living organisms but also provide a key intermediate for controlling the nitrogen balance in cells. The production of amino acids using microorganisms has, along with the development of biotechnology, created a large market for biochemicals. In parallel, there have been various biochemical production methods using pulmonary proteins or direct amino acids as biomass through enzymatic bioconversion or whole-cell biotransformation. The deamination of amino acids facilitated the applications of 2-keto and acrylic acids, in particular, for biofuels of bio alcohol, pharmaceuticals, cosmetics, as building blocks for polymers, and other versatile industrial chemicals. In this review, we report on the application of amino acids derived from biochemicals initiated by deamination reactions using deaminase, ammonia-lyase, and oxidase enzymes for biotechnology applications.
Keywords: Ammonia production; Biotechnology applications; Deamination reaction; Enzymatic bioconversions; Living organisms; Nitrogen balance; Production methods; Whole-cell biotransformations; 2-Keto acids; Acrylic acid; Amino acids; Ammonia; Bio alcohols; Deamination